Evaluation of the Implementation of Independent Learning-Independent Campus (MBKM) Curriculum by Using the CIPP Evaluation Model - Khairi, Ashabul; Jalinus, Niswardi; Ambyar, Ambyar; Waskito, Waskito (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to evaluate the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Curriculum in the PTIK program. This study uses a qualitative approach to the case study at Bung Hatta University. The research data is in the form of the evaluation of the MBKM Curriculum Implementation using the CIPP model. This study collected data through literature studies and interviews with students, lecturers, and heads of PTIK study programs. Evaluation is carried out on the dimensions of the context, input, process, and products of the MBKM curriculum. Evaluation data analysis was conducted with context evaluation, input evaluation, process evaluation, and product evaluation. The research results show that evaluation of the independent curriculum using the CIPP model in the Bung Hatta University PTIK study program by systemizing the evaluation context, input, process, and product evaluation: The context of the curriculum in the PTIK study program is by formulating identification and objectives rather than implementing an independent curriculum. The input step in the Bung Hatta University PTIK Study Program is carried out by analyzing the curriculum's design and structure, reviewing the lecture material offered, and evaluating Human Resources. The evaluation process reviews the independent curriculum, the obstacles encountered while using the curriculum, how students participate, and internal and external responses. Product evaluation is carried out by identifying the results and impacts of the MBKM curriculum, reviewing successes, and identifying the relevance and quality of graduates.